PENANGANAN KERANG HIJAU (Perna viridis) SEBAGAI OLAHAN PRODUK KAMABOKO - Basri, Basri; Rizki, Amin Muhammad (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2023)
Green mussels (Perna viridis) or green mussels are marine inhabitants with two shells and are green in color. Green mussels belong to the class Mytilidae. Animals with a pair of valves are called bivalves. This animal is also known as pelecys which means small axe, and podos which means foot. Green Mussel (Perna viridis) is a type of shellfish that is known to have economic value and excellent nutritional content for consumption, which consists of 40.8% water, 21.9% protein, 14.5% fat, 18.5% carbohydrates, and 4.3% ash, thus making green mussels comparable to beef, eggs or chicken meat, from 100 grams of green mussel meat contains 100 calories. Kamaboko is a typical form of fish from Japan which is generally made from ground fish meat as the main ingredient or infused with clam meat added with starch for thickening, sugar, salt, and sodium glutamate to add flavor. The kamaboko processing involves the stages of dressing, washing, soaking, grinding the shell meat, making the dough, molding, and steaming (cooking).